Feministic Representations Of Double Consciousnessingloria Naylor’s Bailey’s Café - Dr.S.Mahadevan, Dr. P.Tamilarasan (International Journal of Advanced Science and Technology, 2020)
This paper attempts to explore the representations of double consciousness in Gloria Naylor’s Bailey's Cafe It also examines the American consciousness with the double consciousness of being a female and an African-American. It highlights the experiences of the black women. Female is subjected to male desire. They view that black and white are essentially different and the loss of this difference equals the loss of cultural and spiritual identity.Bailey's Cafe is set up in a road side cafe managed by Bailey and his wife. At one level the book is concerned with the often strange stones told by the couple's patrons. The principal theme of the novel according to Naylor is female sexuality. This is relevant when the author examines the lives. Thisnovel has not provoked the heated controversy or accusations of male-bashing that have been generated by her. Though she gives the picturesque of the male domination, physical and mental torture on the women not only of the white but also of the black, the double consciousness persists in all her novels still her men are not objects of radical or instruments of torture. She gives us characters who are at times fools-vain, egocentric, who always make a wrong choice. But such characters are always human, and their numbers can equally be divided between male and female.